A Geochemical Study of Some Igneous Rocks from the Loon Lake Complex Using Spectrographic Methods - McCammon, Barry W. (My University, 1968)
Spectrographic methods have been used to investigate the distribution of some minor elements in a suite of rocks from the Loon Lake pluton in southeastern Chandos Township, County of Peterborough, Ontario, Canada. The rocks studied represent a calc-alkalic series. The elements under investigation include Be, Ga, Cr, Ti, Li, Ni, Co, Cu, V, Zr, Mn, Sc, Y9 Sr, Ba, Rb, and Fe. Their abundances are compared with those determined by other analysts, in particular S.R. Nockolds and R. Allen. The probable host minerals are also considered. Cr, Ti, Ni, Co, V, Mn, and Fe generally are enriched in the basic rocks whereas Rb is generally enriched in the granitic rocks of the series. Fairly even distributions are shown by Ga, Cu, and Y, and no clear trends are indicated for Li, Zr, Sr, Ba, Be, and Sc.
Title: A Geochemical Study of Some Igneous Rocks from the Loon Lake Complex Using Spectrographic Methods, Author: Barry W. McCammon, Location: Thode